One virus, two countries what Covid-19 tells us about South Africa - Friedman, Steven 1953- (Wits University Press, 2021)
Has South Africa 'done well' at limiting illness and deaths during the COVID-19 pandemic? Academic and political commentator, Steven Friedman, thinks not. While the country's mainstream media believes it has, in his view the evidence tells another story. South Africa has experienced by far the most cases and deaths in Africa - at one point as many as the rest of the continent combined. One Virus, Two Countries: What Covid-19 tells us about South Africa offers a searing analysis of government and expert scientists' responses to the pandemic. Friedman argues that South Africa is two societies in one - a 'First World' which resembles Western Europe and North America, and a 'Third World' which looks much like the rest of Africa or South Asia. The South African state, the media and the scientific community have largely tried to deal with the virus through a 'First World' lens in which much of the country was either invisible or a problem - not a partner. Friedman argues this approach prevented the country from responding in a way which would have protected most citizens. This is why case numbers and deaths are so high: South Africa has done worse than the rest of Africa not despite the fact that it has a 'more developed' health system, but because it does. One Virus, Two Countries is a controversial book that will rouse much needed debate about South Africa's health and economic system in a context of serious inequality